The Sorogan Method as a Differentiated Qur’anic Learning Strategy to Enhance Qur’anic Fluency in a Public Madrasah - Amalia, Amanda Rizki; Hasirah; Fahri, Ismail; Thontawi, M. (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
This study examines the Sorogan method as a differentiated Qur’anic learning strategy to enhance Qur’anic reading fluency among eighth-grade students in a public madrasah. Sorogan is an individualized recitation approach in which students read Qur’anic verses directly to the teacher and receive immediate and specific corrective feedback on makhraj articulation and tajwid application. Employing a qualitative descriptive design, the study involved one Qur’an Hadith teacher and 29 students. Data were collected through classroom observations, open-ended interviews, and analysis of instructional documentation over a six-week period. The findings indicate that the Sorogan method supported improvements in reading continuity, accuracy of makhraj articulation, and consistency in applying basic tajwid rules, particularly among students with lower initial fluency. The four initially less-fluent students demonstrated reduced hesitation and fewer recurring pronunciation errors following repeated individualized recitation sessions. In addition to its corrective function, the method enabled the teacher to diagnose specific reading difficulties and provide targeted remedial guidance. Challenges related to limited instructional time and students’ initial lack of confidence were addressed through rotational scheduling and supportive feedback strategies. The study contributes to Qur’anic pedagogy by reconceptualizing Sorogan as a process-based differentiated instructional strategy and a form of formative micro-assessment applicable in formal secondary education settings. Practically, the findings suggest that short and structured Sorogan sessions can be integrated alongside classical instruction to accommodate heterogeneous fluency levels. Future research should employ quantitative or mixed-method approaches using standardized Qur’anic fluency measures and explore implementation across broader educational contexts.